Finite element analysis of the effect of cantilever and implant length on stress distribution in an implant-supported fixed prosthesis - (:unkn) unknown (My University, 1996)
This study investigated the stress distribution at the bone/implant interface with a three-dimensional finite element stress analysis by using three different cantilever and implant lengths in an implant-supported fixed partial denture. Simulation models were created as a bilateral distal cantilever fixed partial denture supported with six implants embedded in a model of the mandibular bone. Nine different simulation models had three different cantilevers (7, 14, and 28 mm) and implant lengths (7, 15, and 20 mm). Vertical forces of 75 N and horizontal forces of 25 N were applied to the distal end of the cantilever. Analysis of the von Mises stresses for the bone/implant interfaces revealed that the maximum stresses occurred at the most distal bone/ implant interface located on the loaded side and significantly increased with the length of the cantilever. However, there was no statistically significant change associated with the length of implants.
Keywords: Humans; Models, Biological; Dental Stress Analysis; Computer Simulation; Dental Prosthesis, Implant-Supported; Denture, Partial, Fixed; Elasticity; Poisson Distribution; Tensile Strength